Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fphar.2021.614465
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Midazolam, Propofol, and Dexmedetomidine in Patients With or at Risk for Acute Respiratory Distress Syndrome: A Propensity Score-Matched Cohort Study

Abstract: Background: Sedatives are commonly used in patients with or at risk for acute respiratory distress syndrome (ARDS) during mechanical ventilation. To systematically compare the outcomes of sedation with midazolam, propofol, and dexmedetomidine in patients with or at risk for ARDS.Methods: We developed a dataset of real-world data to enable the comparison of the effectiveness and safety of sedatives and the associated outcomes from the MIMIC-III database and the eICU Collaborative Research database. We performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Similar to the current study, Hu et al 22 showed that after adjusting for nearly identical clinical factors (age; sex; ethnicity; weight; height; APACHE III score; oxygenation index; alveolar-arterial oxygen difference; patient characteristics at discharge; hospital characteristics like number of beds, teaching, and geographic location), a significant mortality benefit was associated with dexmedetomidine when compared to both propofol (aOR 0.58 [0.42-0.79]; P < 0.001) and midazolam (aOR 0.52 [0.40-0.68]; P < 0.001), while midazolam compared to propofol was not significant (aOR 1.23 [0.96-1.57]; P = 0.10). We are uncertain whether the observed mortality benefit associated with dexmedetomidine, as reported in our study and by Hu et al 22 is due to milder disease severity in the treated patients. This ambiguity arises from the fact that dexmedetomidine, being a relatively light sedative, may not suffice in situations where higher post-end-expiratory pressure (PEEP) is needed, primarily due to the patient's comfort requirements.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the current study, Hu et al 22 showed that after adjusting for nearly identical clinical factors (age; sex; ethnicity; weight; height; APACHE III score; oxygenation index; alveolar-arterial oxygen difference; patient characteristics at discharge; hospital characteristics like number of beds, teaching, and geographic location), a significant mortality benefit was associated with dexmedetomidine when compared to both propofol (aOR 0.58 [0.42-0.79]; P < 0.001) and midazolam (aOR 0.52 [0.40-0.68]; P < 0.001), while midazolam compared to propofol was not significant (aOR 1.23 [0.96-1.57]; P = 0.10). We are uncertain whether the observed mortality benefit associated with dexmedetomidine, as reported in our study and by Hu et al 22 is due to milder disease severity in the treated patients. This ambiguity arises from the fact that dexmedetomidine, being a relatively light sedative, may not suffice in situations where higher post-end-expiratory pressure (PEEP) is needed, primarily due to the patient's comfort requirements.…”
Section: Discussionsupporting
confidence: 90%
“…Estos agentes se metabolizan y eliminan a través de vías que dependen menos de la función hepática (33). Para los pacientes de la UCI que requieren ventilación mecánica a largo plazo , la dexmedetomidina puede reducir significativamente la incidencia de delirio y la aparición de AGI, especialmente para los pacientes obesos , el uso de la sedación con dexmedetomidina tiene poco impacto en su función hepática y el metabolismo de los lípidos en sangre , y puede mejorar significativamente el pronóstico (34) Incluso, la sedación con dexmedetomidina se asoció con una tasa de mortalidad hospitalaria más baja que la sedación con midazolam y propofol o la sedación sin dexmedetomidina ( p < 0,001) (35).…”
Section: Discussionunclassified
“…It could reduce the oxygen consumption of ARDS. A cohort study systematically showed that the risk of death was reduced in patients with ARDS treated with DEX, and it may be the preferred sedative (Hu et al 2021 ). Furthermore, the progression of hypoxemia is associated with pulmonary as well as systemic inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%